2015
DOI: 10.1016/j.ejrnm.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion weighted imaging and dynamic contrast enhanced magnetic resonance imaging in breast tumors

Abstract: Available online xxxx KEYWORDS Breast; Diffusion-weighted imaging (DWI); Dynamic contrast-enhanced MRI (DCE-MRI); Breast MRIAbstract Purpose: To evaluate the role of diffusion weighted imaging and dynamic contrast enhanced magnetic resonance imaging in characterization of breast tumors and comparing the results with the histological finding. Patients and methods: From January 2011 to January 2015, 71 patients with 74 suspicious breast lesions had performed breast DCE-MRI combined with DWI and the results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Accordingly, we were able to achieve a sensitivity of 73%, and specificity of 83.7%. We understand that this specificity was lower when compared to El Bakry et al [29] and Yadav et al [30] who reached a respective specificity of 92.1% and 91.6%.…”
Section: Discussionmentioning
confidence: 57%
“…Accordingly, we were able to achieve a sensitivity of 73%, and specificity of 83.7%. We understand that this specificity was lower when compared to El Bakry et al [29] and Yadav et al [30] who reached a respective specificity of 92.1% and 91.6%.…”
Section: Discussionmentioning
confidence: 57%
“…A further 103 studies were excluded for the study type (not articles), 40 studies were excluded for the language, and 111 studies were excluded for failure to meet the eligibility criteria after carefully reading the full text: failure to extract the number of true positives, false negatives, false negatives, and true negatives; no mp-MRI to diagnose breast cancer; and did not use 1.5-T or 3.0-T MRI machines. Finally, 22 studies were included in the meta-analysis (24,812,1417,2938).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have demonstrated that the number of benign breast lesions among the lesions with type I contrast enhancement kinetic was larger than that among lesions with type II or type III contrast kinetics. It means that the lesions with type I contrast kinetic tend to be benign (36,4042). In addition, the number of malignant breast lesions was larger among the lesions with type III contrast enhancement kinetic than that among the lesions with type I or type II contrast enhancement kinetics (36,4042).…”
Section: Discussionmentioning
confidence: 99%
“…Another study done by Bakry et al . in 2015, to evaluate the role of DWI and DCE-MRI in characterisation of breast tumours, showed a sensitivity of 91.7% and a specificity of 84.2% for DCE-MRI alone [ 14 ]. The diffusion-weighted MRI showed a sensitivity of 94.4% and a specificity of 92.1%.…”
Section: Discussionmentioning
confidence: 99%